The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.21203/rs.3.rs-2118612/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mediating effect of psychological empowerment on the relationship between work environment and clinical decision-making among midwives: A multicentre cross-sectional study

Abstract: Background Clinical decision-making is considered an essential behaviour in clinical practice. However, no research has been done to examine the associations among midwives’ clinical decision-making, work environment and psychological empowerment. Thus, the study aims to determine the influence of work environment on midwives’ clinical decision-making and confirm the mediating role of psychological empowerment. Method 602 registered midwives from 25 public hospitals in China were included in this multicentre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(44 reference statements)
1
0
0
Order By: Relevance
“…Pearson's correlation analysis revealed significant positive correlations between spiritual climate and psychological empowerment as well as its four dimensions; accordingly, the better the nurses' perceived spiritual climate was, the higher the level of psychological empowerment they exhibited, a finding which is in line with the results of previous studies on the relationships among the organizational climate, a healthy work environment and psychological empowerment [43,44]. Susuki et al [45] surveyed half-time nurses working in a Japanese hospital and found that a positive and diverse climate in the workplace allowed these nurses to express their ideas about working, which was necessary for enhancing their psychological empowerment.…”
Section: Discussionsupporting
confidence: 88%
“…Pearson's correlation analysis revealed significant positive correlations between spiritual climate and psychological empowerment as well as its four dimensions; accordingly, the better the nurses' perceived spiritual climate was, the higher the level of psychological empowerment they exhibited, a finding which is in line with the results of previous studies on the relationships among the organizational climate, a healthy work environment and psychological empowerment [43,44]. Susuki et al [45] surveyed half-time nurses working in a Japanese hospital and found that a positive and diverse climate in the workplace allowed these nurses to express their ideas about working, which was necessary for enhancing their psychological empowerment.…”
Section: Discussionsupporting
confidence: 88%
“…Nurses with the highest PE were the most flexible in CDM. For instance, in the context of inappropriate management of decision-making, Zeng et al conducted a multicenter cross-sectional study and suggested that PE was positively associated with CDM [30]. This indicates that nursing staff can make decisions and manage their affairs to pursue significant and worthwhile career objectives.…”
Section: The Relationship Between Nurses' Pe and Cdmmentioning
confidence: 99%